Controlled preparation of a cd(II) coordination polymer via green sonochemical synthesis: new precursors for the preparation of cadmium(II) oxide. Issue 15 (17th December 2021) - Souri, Bagher; Abbasi, Soheila; Hayati, Payam; Farsadrooh, Majid; Rezvani, Ali Reza; Centore, Roberto
Abstract: A 2 D cadmium(II) coordination polymer (CP), [Cd(N3 )(L)]n (1 ) [L = picolinato] was synthesized by the branch tube method. Nano and microstructures of 1 were synthesized by sonochemical technique in various conditions (different times and solvents) and were identified by elemental analysis, FT-IR spectra, scanning electron microscopy (SEM), and powder X-ray diffraction (PXRD). The effects of time of reaction and solvent on the size and morphology of the nano and microstructures of 1 were also evaluated. The results showed that change in solvent leads to changes in the morphology of structures, while the change in reaction time was effective on the size of the structures. Therefore, the morphology of 1 is solvent-dependent. Graphical Abstract: UF0001